Analisis Semiotika Pada Perubahan Logo Partai Amanat Nasional Dengan Ikon Semangka Di Media Instagram @amanatnasional - Adimas Surya; Yusril Sahendra (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Semiotics is concerned with providing an interpretation that can be recognized through the signs displayed from symbols. The method used in this research is a descriptive qualitative method with a semiotic analysis approach. The logo analyzed was the Partai Amanat Nasional logo, going from the old logo to the new logo within the period determined by the researchers, namely November 7 to November 12. Researchers used this approach due to analysis of the logo shape of the Partai Amanat Nasional. The semiotic analysis used in this research is Charles Sanders Peirce's analysis because the researcher will specifically study and analyze the logo of the Partai Amanat Nasional. The findings show that the signs in the Partai Amanat Nasional logo design can be identified by applying colours, symbols and typography to convey support for Palestine. The image of a combination of a sign with a letter in the shape of the letter becomes a symbolic combination carried out on the PAN logo using a watermelon icon replacing the letter A. This can represent a concern for the problems that exist in Palestine.